2012
DOI: 10.4067/s0718-34022012000100005
|View full text |Cite
|
Sign up to set email alerts
|

La participación política de los residentes británicos y alemanes en España: el caso de San Miguel de Salinas, Alicante

Abstract: RESUMENditerránea de Alicante que tienen un estatus más cercano al de un inmigrante que al de un turista. La importancia que ha cobrado esta corriente inmigratoria ha provocado cambios profundos en muchos municipios. El objetivo es estudiar el papel político de estos ciudadanos en aquellas regiones en las que su presencia es las elecciones municipales de 2011 y en un trabajo cualitativo que ahonda en la comprensión de los procesos informales de participación política. El hecho de que de los extranjeros por par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…The low turnout of foreign voters in the 2011 municipal elections led to questions about the effectiveness of the conventional reciprocity model for extending foreign suffrage, possibly due in part to the requirement of prior enrolment on the voting register (Méndez, 2008;Moya and Viñas, 2012). The low influence of the immigrant population in local political institutions, at least in the case of Northern European residents, seems to be related to their lack of interest in public life, an attitude encouraged by the political elites (Huete and Mantecón, 2012). Studies have confirmed that the low turnout registered in municipal elections was repeated in the 2015 elections, when the number of non-EU foreign voters decreased, due to the rise in nationalizations and exits from the country following the economic crisis (Bermúdez and Escrivá, 2016).…”
Section: Political Participation: Spain's "New Voters"mentioning
confidence: 99%
“…The low turnout of foreign voters in the 2011 municipal elections led to questions about the effectiveness of the conventional reciprocity model for extending foreign suffrage, possibly due in part to the requirement of prior enrolment on the voting register (Méndez, 2008;Moya and Viñas, 2012). The low influence of the immigrant population in local political institutions, at least in the case of Northern European residents, seems to be related to their lack of interest in public life, an attitude encouraged by the political elites (Huete and Mantecón, 2012). Studies have confirmed that the low turnout registered in municipal elections was repeated in the 2015 elections, when the number of non-EU foreign voters decreased, due to the rise in nationalizations and exits from the country following the economic crisis (Bermúdez and Escrivá, 2016).…”
Section: Political Participation: Spain's "New Voters"mentioning
confidence: 99%
“…Since its perceived scale is an evolving composite of political, judicial, economic, and media factors, I cannot report on its incidence here, only report its perceived prevalence. Alicantine sociologists argue that over the last thirty years the devolution of powers from higher to municipal levels of government has enabled corruption to spread (Huete & Mantecón : 91). One British councillor stated that in the 2011 elections, the till‐then governing party and the opposition forces won four seats apiece, making him ‘the key’: that is, his support would open the door to the town hall for either faction.…”
Section: Brits Abroad In Town Hallsmentioning
confidence: 99%
“…Alicantine sociologists, in turn, refer to a ‘deficit in the quality of local democracy’ (Huete & Mantecón : 89).…”
Section: Brits Abroad In Town Hallsmentioning
confidence: 99%
“…Si bien algunas investigaciones se han ocupado de forma parcial de los turistas residenciales de origen alemán, tanto en la Costa del Sol (Rodríguez et al, 1998) como a escala nacional (Garau Vadell & De Juan Videgaray, 2017), ninguno le ha dado atención exclusiva a excepción de Kissel (2001) y Kordel (2016), aunque solo sobre poblaciones ancianas y con enfoques muy específicos. En cambio, la producción científica sobre alemanes turistas o residentes en el extranjero es prolífica y sus enfoques son variados (Sastre, 2012;Huete & Mantecón, 2012;Dijst et al, 2005;Haas, 2015;Hannonen, 2018;Breuer, 2005;Müller, 2002;Jaisuekun & Sunanta, 2016).…”
Section: Introductionunclassified